Regulating systemic risk - Masahiro Kawai; Michael Pomerleano (Asian Development Bank Institute (ADBI), 2010)
The failure to spot emerging systemic risk and prevent the current global financial crisis warrants a reexamination of the approach taken so far to crisis prevention. The paper argues that financial crises can be prevented, as they build up over time due to policy mistakes and eventually erupt in slow motion. While one cannot predict the precise timing of crises, one can avert them by identifying and dealing with sources of instability. For this purpose, policymakers need to strengthen top-down macroprudential supervision, complemented by bottom-up microprudential supervision. The paper explores such a strategy and the institutional setting required to implement it at the national level. Given that the recent regulatory reforms that have been undertaken to address systemic risks are inadequate to prevent and combat future crises, the paper argues that national measures to promote financial stability are crucial and that the Westphalian principles governing international financial oversight should be rejected. The paper proposes that while an effective national systemic regulator should be established, strong international cooperation is indispensable for financial stability.
Keywords: G01; G21; G28; 330; Finanzmarktkrise; Systemrisiko; Kapitalmarktliberalisierung; Regulierung; Weltwirtschaftsordnung; Welt